Decision support for the selection of measures according to the requirements of the EU Water Framework Directive - Bernd Klauer; Michael Rode; Uwe Franko; Melanie Mewes; Johannes Schiller (Helmholtz-Zentrum für Umweltforschung (UFZ), 2010)
One of the major scientific challenges posed by the EU Water Framework Directive (WFD) is the de-sign of a decision support process that meets the directive's requirement to achieve good status using a cost-effective combination of measures. This paper presents BASINFORM, a new decision tool for selecting cost-effective management measures that has been developed in close co-operation with a number of water authorities and tested in the 5154 km² mesoscale 4th order river Weisse Elster in central Germany. BASINFORM comprises (i) a set procedure for framing the problem concerned, including proposals for quantifying the discrepancy between the status quo and the good water status to be achieved (i.e. the need for action); (ii) modelling tools quantifying the impacts of management measures (e.g. Meta-CANDY and WASP 5); and (iii) a method for selecting cost-effective combina-tions of measures. A trial run of BASINFORM in the Weisse Elster catchment revealed that (i) good surface water status with respect to nutrients can not be achieved if only the "standard" actions of current water management are taken to reduce point sources (sewage treatment) and diffuse agricul-tural sources and (ii) the available measures for nutrient reduction will generate considerable costs. The testing of BASINFORM in the case study proved its practical applicability in the WFD implementa-tion process.
Keywords: 330; EU Water Framework Directive; cost effectiveness; decision support system; decision making; point and non-point pollution; BASINFORM; Meta-CANDY; WASP 5; Gewässerschutz; Management-Informationssystem; Kosten-Nutzen-Analyse